Resource provision and quality of cybersecurity specialists’ training in the Ukrainian HEI as a prerequisite for participation in state programs of the educational specialty development - Potii, Oleksandr; Bakalynsky, Oleksandr; Myalkovsky, Danylo; Verba , Denys (Ukrainian Scientific Journal of Information Security, 2021)
The article is devoted to a review of the preconditions that domestic High Education Institutions (HEI), where the specialty 125 "Cybersecurity" is licensed, have for quality training of the specialists, having appropriate qualifications, in connection with the characteristics of training quality (HEI position in the consolidated ranking of Ukrainian universities). Such preconditions include the scale of educational activities of the HEI, their specialization and compliance of the Department specialization with Passport of specialty 125 "Cybersecurity", the provision of the educational process by teachers with PhD and doctoral degrees. Aggregated, suitable for comparison assessment of resource potential of HEIs for high-quality training of cybersecurity specialists and indicators of such potential realization were calculated. According to the results the 56 HEIs, where cybersecurity specialists are trained, were divided into four groups. The first group includes HEIs, which occupy leading positions both in the presence of preconditions for quality training of cybersecurity professionals, and in assessing the quality of training. The second group includes HEIs that have higher than average, but not the best indicators of preconditions for quality training of cybersecurity professionals, and high indicators of training quality: such positioning indicates the successful implementation of medium and higher than medium potential. The third group includes HEIs who occupy high positions in the ranking of the quality of training, having the worse than median preconditions for quality training of cybersecurity professionals. Finally, the fourth group includes HEIs, which according to the available data do not have sufficient preconditions for high-quality training of cybersecurity specialists, which is confirmed by their positions in the consolidated ranking of Ukrainian universities.